PENDAYAGUNAAN HUKUM DALAM MENGATASI PERILAKU TIDAK RAMAH LINGKUNGAN DALAM PEMANFAATAN SUMBERDAYA IKAN - Marhaeni Ria Siombo (Masalah-Masalah Hukum, 2011)
Geographical conditions of Indonesia as an archipelago of two-thirds of ifs territory is ocean waters, consisting of coastal sea, seas, bays and straits, has 95 181 km long coast, with an area ofiiJS. 8 miflion km2 wafers. The position of the Indonesian seas located in the equatorial and tropical climates if is rich in consequences and potential types of fisheries resources. Ideally, these conditions describe the level of welfare of fishermen in a good rate. But in fact f he fishermen as a group of people living in coastal areas, generally the level of welfare is still very low, as well as level of education and low knowledge in the utilization and management of fish resources. Low knowledge of fishing methods that are environmentally friendly, being one of the causes of destructive fishing. Destructive fishing practices are very dangerous because the damage to marine ecosystems, destroying coral reefs which is a gathering place and breeding fish. ff the arrest is not environmentally friendly is continuing but lower quality fish, the more severe the impact is decreased in quantity the number and type, which one day even be extinct. This requires adequate regulation of government, which reach the public behavior of fishermen to consciously not do fishing that is not environmentally friendly. Government policy to maintain the availability of fish resources through various forms of regulation in the areas of arrest, and how fishermen can organize themselves so that the welfarelevel is better.